Political Will Implementation of The Government in Hope Family Program Policy - Fauzan Ali Rasyid; Moh. Dulkiah (Universitas Sultan Ageng Tirtayasa, 2020)
This article focuses on the study of the government's political will in Program Keluarga Harapan (PKH) policy. The purpose of this study is trying to understand the form of political will of the central government in poverty alleviation through PKH policies. This research method uses descriptive qualitative research methods that take research objects at the district level. The findings of this study can be classified into the following: First, poverty alleviation policies through PKH correlate with improvements in the standard of living of people in terms of education, economics, and health. Second, the implementation of PKH which aims to improve the socio-economic welfare of Very Poor Households is still loaded with political interests. Third, the government's political will is still limited to aspects of policy and not yet optimal in aspects of its implementation. This study concludes that the government's political will is not correlated with increasing the welfare of beneficiaries from very poor households.